ANALISIS SISTEM APRAISAL PADA ARTIKEL PORTAL BERITA ONLINE LIPUTAN 6 YANG BERJUDUL CLAUDIA SI CANTIK PEMIMPIN KARTEL NARKOBA MIRIP KIM KARDASHIAN - Muhammad Aprianto Budie Nugroho (Prasasti: Journal of Linguistics)
This reserach focus on apprasisal system analysis on an article entitled”Claudia si cantik pemimpin kartel narkoba mirip Kim Kadarshian”. In this reserach the researcher uses descriptive qualitative method, the data is taken form the news portal liputan6.com that’s afiliated in Surya Citra Televisi (SCTV). That text is analyzed by using appraisal system that focuse on attitude (affect, judgement, and appreciation) amplifying  attitude and source of attitude (graduation). The result of this reserach shows that there are many positive apresiataion on Claudia eventhough Claudia is a drug lord.